The Strategic Bombing of German Cities during World War II and its Impact for Germany - Harry Garretsen; Marc Schramm; Steven Brakman (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2003)
We construct a unique data set in order to analyze whether or not a large temporary shock has an impact on city growth. Following recent work by Davis and Weinstein (2002) on Japan, we take the strategic bombing of German cities during WWII as an example of such a shock, and analyze its impact on post-war German city growth. If the war shock has only a temporary impact, then there will be a tendency towards mean reversion. Our main finding is that the bombing had a significant but temporary impact on post-war city growth in Germany as a whole as well as in western Germany separately (FRG), but that this is not the case for city growth in eastern Germany (GDR).
Keywords: 330; city-growth; mean reversion; WWII bombing of German cities